Victimisation of African Foreign Nationals in Durban, South Africa - Balgobind Singh, Shanta (International Journal of Criminology and Sociology, 2022)
Media reports of the continued violence and discrimination experienced by African Foreign Nationals1 in South Africa have brought into the forefront victimisation of this sector, despite pledges by the government and law enforcement agencies to put a stop to it. This is also linked to current social milieu debates taking place within international trends on migration. Studies and evidence have shown that although the attitudes towards foreign nationals vary across South Africa’s socio-economic and ethnic spectrum, foreigners who live and work in South Africa do face discrimination by citizens, some government officials, members of the police, and by private organisations who are contracted to manage their detention and deportation. This research, with a qualitative approach, explores the persistent issues that threaten African Foreign Nationals. Fifty participants were selected through a purposive sampling technique. The main aim of this research was to examine the issues that threatened the safety and security of African Foreign Nationals in Durban, South Africa. It was found that offences such as physical assault (i.e. Grievous Bodily Harm - GBH), arson, rape, verbal abuse, house robberies, property damage as well as discrimination were serious crimes perpetrated against African Foreign Nationals which was often characterised by xenophobic violent attacks against them.